(untitled) (CIPEEX, 2024)
OBJECTIVE: THIS STUDY AIMS TO EXPLORE THE FUNDAMENTAL ROLE OF EVIDENCE-BASED MEDICINE (EBM) IN PROMOTING THE SUSTAINABILITY OF HEALTHCARE SYSTEMS, WITH AN EMPHASIS ON RESOURCE OPTIMIZATION, PREVENTION OF MEDICAL ERRORS, POPULATION HEALTH PROMOTION, AND THE DEVELOPMENT OF EFFECTIVE CLINICAL GUIDELINES. METHODOLOGY: THIS IS AN INTEGRATIVE LITERATURE REVIEW, SEEKING ARTICLES PUBLISHED WITHIN THE LAST 5 YEARS IN THE PUBMED AND VIRTUAL HEALTH LIBRARY (VHL) DATABASES, USING THE HEALTH DESCRIPTORS " ADMINISTRATIVE CLAIMS, HEALTHCARE " AND "EVIDENCE-BASED MEDICINE." FOUR ARTICLES WERE SELECTED FOR THIS WORK. TO ACHIEVE OUR OBJECTIVE, WE CONDUCTED A LITERATURE REVIEW THAT ADDRESSED RELEVANT PRIMARY AND SECONDARY SCIENTIFIC RESEARCH ON THE APPLICATION OF EBM IN HEALTHCARE SYSTEMS. OUR REVIEW COVERED A WIDE RANGE OF TOPICS, INCLUDING THE EFFECTIVENESS AND SAFETY OF MEDICAL TREATMENTS, VIRTUAL HEALTHCARE, AND ITS IMPACTS ON HEALTHCARE SYSTEMS, EVIDENCE-BASED HEALTH POLICIES, PREVENTION OF MEDICAL ERRORS, AND THE DEVELOPMENT OF CLINICAL GUIDELINES. RESULTS: EBM PLAYS A CRUCIAL ROLE IN OPTIMIZING HEALTHCARE SYSTEM RESOURCES. BY IDENTIFYING INEFFECTIVE OR UNNECESSARY MEDICAL PRACTICES, EBM CONTRIBUTES TO SUBSTANTIAL COST SAVINGS IN HEALTHCARE EXPENDITURES. THE ELIMINATION OF UNNECESSARY TESTS, PROCEDURES, OR TREATMENTS RESULTS IN A MORE EFFICIENT ALLOCATION OF FINANCIAL RESOURCES. FURTHERMORE, EBM PLAYS A SIGNIFICANT ROLE IN PREVENTING MEDICAL ERRORS BY IDENTIFYING BEST PRACTICES AND PROTOCOLS, REDUCING THE INCIDENCE OF HARMFUL MEDICAL ERRORS. POPULATION HEALTH PROMOTION IS ANOTHER SIGNIFICANT BENEFIT OF EBM. AN EVIDENCE-BASED APPROACH PROVIDES A SOLID FOUNDATION FOR EFFECTIVE PUBLIC HEALTH POLICIES. BY IDENTIFYING PROVEN INTERVENTIONS, EBM CAN IMPROVE POPULATION HEALTH WHILE SIMULTANEOUSLY CONSERVING RESOURCES BY AVOIDING INEFFECTIVE STRATEGIES. MOREOVER, EBM FACILITATES THE DEVELOPMENT OF EFFECTIVE CLINICAL GUIDELINES. THESE GUIDELINES ENABLE HEALTHCARE PROFESSIONALS TO DELIVER HIGH-QUALITY CARE ALIGNED WITH THE BEST AVAILABLE EVIDENCE, RESULTING IN BETTER OUTCOMES FOR PATIENTS AND A REDUCTION IN UNNECESSARY CLINICAL VARIATION. CONCLUSIONS: THE APPLICATION OF EVIDENCE-BASED MEDICINE IS CRITICALLY IMPORTANT FOR THE SUSTAINABILITY OF HEALTHCARE SYSTEMS. BY EMPHASIZING THE EFFECTIVENESS, EFFICIENCY, AND SAFETY OF TREATMENTS, EBM NOT ONLY ENHANCES THE QUALITY OF HEALTHCARE BUT ALSO SIGNIFICANTLY CONTRIBUTES TO FINANCIAL SUSTAINABILITY AND THE PROMOTION OF A HEALTHIER POPULATION. THE CONTINUED INTEGRATION OF EBM INTO CLINICAL DECISION-MAKING AND HEALTHCARE POLICIES IS ESSENTIAL TO ENSURE THAT OUR HEALTHCARE SYSTEMS REMAIN RESILIENT AND CAPABLE OF MEETING THE PRESENT AND FUTURE NEEDS OF SOCIETY.